The market for non-alcoholic wine in Germany – Structural analysis and implications for competitive strategies - Frederik Nikolai Schulz; Jon H. Hanf (Wine Economics and Policy)
Non-alcoholic wines have become increasingly important in recent years in Germany. A constant stream of new market players and products is evidence of a dynamic market development and for the creation of a new branch in the highly competitive wine sector. Thus, the central aim of this article is to provide a first analysis of the structure of the German market for non-alcoholic wines in order to derive implications for industry competition and possible competitive strategies of individual market participants. An explorative research approach has been applied including in-depth interviews with experts from various companies along the value chain (n=24). Results show that competition in the market for non-alcoholic wines must be regarded as dynamic due to strong external market forces. A high risk of new companies entering the market can be emphasised as well as the high bargaining power of the retail and a high threat of substitutes. Within the industry, however, rivalry is currently con-sidered to be low, resulting in low profitability and a tendency towards high fluctuation of market participants. With regard to possible competitive strategies it becomes clear that especially for smaller wineries, a long-term successful survival within the market can only be realised with strong differentiation. Ultimately, the transfer of the products into an own category which departs from the classic image of non-alcoholic wine represents a promising approach in order to address entirely new target groups.